A novel and sensitive turn-on fluorescent biosensor for the determination of thioctic acid based on Cu2+-modulated N-acetyl-l-cysteine capped CdTe quantum dots1. Issue 55 (17th June 2015) - Tan, Xuanping; Li, Qin; Zhang, Xiaoning; Shen, Yizhong; Yang, Jidong
<x xml:space="preserve">Abstract</x> A new fluorescence sensor for the determination of thioctic acid (TA) in aqueous media based on the recovered fluorescence of N-acetyl-l-cysteine capped CdTe quantum dots [NALC-CdTe QDs]–Cu2+ system was proposed.